The Influence of Work Culture and Knowledge Sharing Systems on the Performance of Bango Sale MSME Employees in Bungo Regency - Supriyati Supriyati; Heriyanto, Heriyanto; Darham Wahid; Nurmala Sari; Yudhi Novriansyah (Dinasti Publisher, 2024)
Through the proper use of Human Resources (HR), it is hoped that Micro, Small and Medium Enterprises (MSMEs) Banana Sale in Bungo Regency can further expand their marketing and be able to compete to become superior local products. The aim of this research is to determine the influence of Work Culture and Knowledge Sharing on the Performance of UMKM Pisang Sale Employees in Bungo Regency. This research method is Quantitative Explanatory using multiple linear regression analysis with a research sample of 104 people. The results of this research show that the regression equation formed is Y = 11.714+ 0.109X1 + 0.897 X2. The F-calculated value is 83.170 > F-table is 3.09, then H0 is rejected and Ha is accepted, meaning that Work Culture (X1) and Knowledge Sharing (X2) influence Employee Performance (Y) of UMKM Pisang Sale. The R Square value is 0.622 or 62.2%, where the two independent variables contribute 62.2% to employee performance, while the remaining 37.8% is influenced by other factors outside this research.